Pericecal herniation of sigmoid colon diagnosed by computed tomography: Two case reports - Lee, Ji Eun (Medicine (Baltimore), 2018)
INTRODUCTION: Computed tomography (CT) plays an important role in diagnosing specific types of internal hernias and their complications. In particular, pericecal hernia of the sigmoid colon has never been reported in the English literature. CASE PRESENTATION: The first patient was a 46-year-old female presented to our institution due to acute abdominal pain. The second patient was a 55-year-old male presented to our institution with continuous diarrhea. The patient underwent colonoscopy for further evaluation. However, even with sufficient air insufflation and repetitive maneuvers, the colonoscope could not proceed beyond the narrowed level of the sigmoid colon. In both cases, contrast-enhanced abdominal CT was done and a herniated loop of sigmoid colon was noted in the posterolateral aspect of the cecum and ascending colon. Thus, a diagnosis of pericecal herniation of the sigmoid colon was established. CONCLUSION: This case study indicates that radiologic examination can be helpful in detecting pericecal herniation of the sigmoid colon.